2021
DOI: 10.1039/d1nr00544h
|View full text |Cite
|
Sign up to set email alerts
|

Electrical energy generation by squeezing a graphene-based aerogel in an electrolyte

Abstract: Mechanical energy harvesters are widely studied because of their diverse applications, such as harvesting of ocean wave energy, self-powered wireless sensors, portable power supplies and so on. To be feasible,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…GO contains a variety of oxygen functional groups, and their interaction with lithium ions can increase the dissociation of lithium salts and thus can increase the ionic conductivity. In addition, it has been reported that it is possible for lithium ions to find low-energy conduction paths along the interface between the carbon-based filler and the polymer matrix . Meanwhile, it can be found from Figure S2 that the mechanical properties of large-sized graphene sheets are relatively better, which is another reason for choosing large-sized graphene sheets.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…GO contains a variety of oxygen functional groups, and their interaction with lithium ions can increase the dissociation of lithium salts and thus can increase the ionic conductivity. In addition, it has been reported that it is possible for lithium ions to find low-energy conduction paths along the interface between the carbon-based filler and the polymer matrix . Meanwhile, it can be found from Figure S2 that the mechanical properties of large-sized graphene sheets are relatively better, which is another reason for choosing large-sized graphene sheets.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been reported that it is possible for lithium ions to find lowenergy conduction paths along the interface between the carbon-based filler and the polymer matrix. 30 Meanwhile, it can be found from Figure S2 that the mechanical properties of large-sized graphene sheets are relatively better, which is another reason for choosing large-sized graphene sheets.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 f). This specific weight power density even holds advantages when compared to that of state-of-the-art environmental energy harvesters [ 35 42 ]. Selected representative reports are summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%